La transición de las ciudades: pasado, presente y futuro de la forma urbana (2019)
The article analyses the origin and evolution of the urban form from a well-defined variable: transitions. In the introduction it is clarified that the transitions studied correspond to dimensions that overcome the traditional concept of transition that only takes into account the transition from the rural to the urban. The methodology includes four moments, the fourth being the formulation of predictions about the cities of 2050. The results address three themes: i) origins and evolution of urban transitions; ii) the future of the cities: cinematographic referents; and iii) cities in 2050. It is concluded that the transitions and the evolution of the urban form have had close ties throughout history, and precisely, thanks to the transitions, the cities consolidated and evolved to the current state, and will contin-ue to transform in the future.